A new endoprosthesis for the Vosschulte operation.: description, technique and results - Liard, Washington; Balboa, Oscar; Puig, Roberto; Perdomo, Roberto (Cirugía del Uruguay, 1976)
The authors present the procedure of Vossschulte, for the surgical treatment of esophageal varices, consistent in the interruption of the portal venous · flow in the esophagic terr!tory, by means of the total ligature of the esophagus, over a transitory and eliminable prosthesis designated to maintain the transit. This technique was realized with modifications. The authors introduce a new dispositive of prosthesis with advantages over the metal rings previously used, demonstrated in a serie of cases: low cost, null agresivity, antireflux mechanism, good elimination and facility of improvisation, with short material resources.